A new Cu(II)-based energetic complex constructed using mixed building blocks: Synthesis, structure and standard molar enthalpy of formation. (1st January 2019) - Wu, Shuo; Lin, Guowei; Ge, Yihao; Yang, Zhengyi; Yang, Qi; Wei, Qing; Xie, Gang; Chen, Sanping; Gao, Shengli; Lu, Jack Y.
Graphical abstract: Based on the solution calorimetry, the standard molar enthalpy of formation of a new Cu(II) energetic complex constructed by mixed building blocks was determined. The calculated detonation properties show it can be a candidate used in the field of energetic materials. Abstract: A new energetic complex, Cu(TO)2 (HDNBA)2 (DNBA)2 (1) (TO = 1, 2, 4-triazole-5-one, HDNBA = 3, 5-dinitrobenzoic acid), has been synthesized and characterized. Structural analysis reveals that1 possesses a 3D supermolecular architecture with mononuclear Cu(II) unit and mixed building blocks. TG and DSC analyses of1 display a rapidly one-step thermal decomposition process and relatively high thermostability up to 498 K. The non-isothermal kinetics of exothermic decomposition process of1 was studied. Based on the solution calorimetry, a thermochemical cycle was designed to determine the enthalpies of solution of reactants and products of coordination reaction of1 by using a RD496-2000 microcalorimeter at 298.15 K. The standard molar enthalpy of formation of1 was determined to be −(1585.7 ± 2.3) kJ·mol −1 . The detonation properties of1 were calculated by an effective empirical method using the standard molar enthalpy of formation. The calculated heat of detonation of1 is equivalent to that of TNT and higher than some known energetic complexes, such as CHHP and ZnHHP.